METODE PENGAJARAN MENGGUNAKAN MODEL AUDISI PENCARIAN BAKAT DI TELEVISI - Ali Taufik; Suid Saidi (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2021)
TEACHING METHODS USING THE TELEVISION TALENT SEARCH AUDITION MODELThe  main purpose of this study was to answer the five (5) questions the research on: Motivation, Achievement, competition, prestige (esteem) and orderly time, will be missed on the research results, in addition to the collaboration between the teaching style audition with, the development of a model audition   that of the entertainment program on television. This research study is to do a collaboration between teaching style audition to audition models program  television.The study the authors chose a model using fenomenology, in an effort to further explore the internal factors and external factors of the participants individually, so not just displaying figures on the above calculation paper. Findings   From the results obtained from processing of data and calculation of the amount of value as well as the interview shows the results of the acquisition value the better of each meeting seen this from the value that was obtained, at a meeting of the audition stage three (3), already visible once the values are moving fluctuating. Significance  those who scored high and moderate increased while the low score decreased, indicating a significant change, after combining teaching methods and audition models such as television programs (talent shows)., There was a significant increase.